Enamel chipping in Taï Forest cercopithecids: Implications for diet reconstruction in paleoanthropological contexts. Issue 141 (April 2020) - Fannin, Luke D.; Guatelli-Steinberg, Debbie; Geissler, Elise; Morse, Paul E.; Constantino, Paul J.; McGraw, W. Scott
Abstract: Antemortem enamel chipping in living and fossil primates is often interpreted as evidence of hard-object feeding (i.e., 'durophagy'). Laboratory analyses of tooth fracture have modeled the theoretical diets and loading conditions that may produce such chips. Previous chipping studies of nonhuman primates tend to combine populations into species samples, despite the fact that species can vary significantly in diet across their ranges. Chipping is yet to be analyzed across population-specific species samples for which long-term dietary data are available. Here, we test the association between enamel chipping and diet in a community of cercopithecid primates inhabiting the Taï Forest, Ivory Coast. We examined fourth premolars and first molars ( n  = 867) from naturally deceased specimens of Cercocebus atys, Colobus polykomos, Piliocolobus badius, Procolobus verus, and three species of Cercopithecus . We found little support for a predictive relationship between enamel chipping and diet across the entire Taï monkey community. Cercocebus atys, a dedicated hard-object feeder, exhibited the highest frequencies of (1) chipped teeth and (2) chips of large size; however, the other monkey with a significant degree of granivory, Co. polykomos, exhibited the lowest chip frequency. In addition, primates with little evidence of mechanically challenging or hard-food diets—such as Cercopithecus spp., Pi. badius, and Pr. verus —evinced higher chipping frequencies than expected. The equivocal and stochastic nature of enamel chipping in the Taï monkeys suggests nondietary factors contribute significantly to chipping. A negative association between canopy preference and chipping suggests a role of exogenous particles in chip formation, whereby taxa foraging closer to the forest floor encounter more errant particulates during feeding than species foraging in higher strata. We conclude that current enamel chipping models may provide insight into the diets of fossil primates, but only in cases of extreme durophagy. Given the role of nondietary factors in chip formation, our ability to reliably reconstruct a range of diets from a gradient of chipping in fossil taxa is likely weak.